Intrinsically High Magnetic Performance in Core–Shell Structural (Sm, Y)Fe12‐Based Permanent Magnets. Issue 28 (7th June 2022) - Zhao, Lizhong; Su, Rui; Wen, Lin; Li, Wei; Liu, Xiaolian; Zhang, Zhenhua; Zhao, Rongzhi; Han, Yuyan; Zhang, Xuefeng; Li, Wei
Abstract: ThMn12 ‐type SmFe12 ‐based permanent magnets have exhibited great potential in advanced magnet motors because of their high temperature stability of magnetic properties. However, the applications could be seriously limited due to the trade‐off between phase stability and intrinsic magnetic properties. In this work, an effective solution is demonstrated by constructing the core–shell structure (Sm‐rich shell and Y‐rich core) via a spontaneous spinodal decomposition process. The anisotropy field for the (Sm0.75 Y0.25 )(Fe0.8 Co0.2 )11.25 Ti0.75 alloy is mostly optimized to be 9.24 T at room temperature. Such an enhancement is ascribed to the pinning process of domain walls by the magnetic‐hardening Sm‐rich shell, which is directly observed by in situ Lorentz transmission electron microscopy and reconstructed by micromagnetic simulation. Moreover, the phase stability and saturation magnetization are simultaneously increased, which is attributed to the synergistic effect of Y, Co, and Ti substitutions. More importantly, the high μ0 M s value of 1.52 T is comparable to the reported (Sm, Zr)Fe12 ‐based bulk alloys that contain a larger amount of soft α‐Fe phases, indicating that this strategy is more promising toward bulk magnets. The present study provides a significant concept for the development of advanced permanent magnets and also has implications for understanding the structural origin of intrinsic magnetic configurations. Abstract : The construction of core–shell structure (Sm‐rich shell and Y‐rich core) in (Sm, Y)Fe12 ‐based magnet is demonstrated via a spontaneous spinodal decomposition process, resulting in the relatively high anisotropy field of 9.24 T in the optimized alloy. It provides an innovative strategy and has important significance for the design of high‐performance magnets.